Mobile Money, Financial Inclusion, and Unmet Opportunities: Evidence from Uganda - Hamdan, Jana S; Lehmann-Uschner, Katharina; Menkhoff, Lukas (Routledge, 2022)
Mobile money is an important instrument to improve the degree of financial inclusion, especially in developing countries. However, having a mobile money account does not imply that this account is actually used. In our sample, 86% of microentrepreneurs own a mobile money account, but only 49% actively use it – the resulting gap indicates unmet opportunities. We estimate that mobile money reaches up to 40% of those without prior access to (semi-)formal financial services, still leaving a substantial group behind in which women and the most disadvantaged are overrepresented. A choice experiment shows that high fees hinder mobile money usage for a substantial number of microentrepreneurs. Moreover, insufficient physical infrastructure, i.e. a small number and unfavourable spatial distribution of mobile money agents, also limits access, while a lack of financial education seems to contribute to comparatively low price sensitivity. Based on these results, we suggest policy measures that reduce the remaining barriers limiting the contribution of mobile money to financial inclusion.
Keywords: Financial inclusion, mobile money, microentrepreneurs, choice experiment